Efektivitas Pembelajaran Fiqih dengan Mengunakan Metode Demonstrasi di Madrasah Ibtidaiyah Negeri Desa Penggage-Muba - Ema Amalia; Ibrahim Ibrahim (JIP Jurnal Ilmiah PGMI, 2017)
The lesson of Fiqh by using the method of demonstration in Class IV Madrasah IbtidaiyahNegeri DesaPenggage with the aim of research that is to know the use of demonstration method so that it can be effective learning of fiqh. The method used is field research method. The subjects of this field research are students of fourth grade Madrasah IbtidaiyahNegeriDesa Penggage with the type of quantitative descriptive research, where the results are presented in numerical form and clarified with narrative descriptive. The population of this study is all students of Class IV MIN DesaPenggage. Data collection techniques were conducted using observation methods, interviews, questionnaires, documentation and test techniques. While the data analysis technique used is the analysis of test "t" and get the result that the method of demonstration used as a method that can streamline the learning of fiqh and give a positive impact.